The Social and Aesthetic Aspects of Avant-Garde Music According to Leopoldo Hurtado: His Critical View in Revista de Arte (1936) and Other Texts (Revista Argentina de Musicología, 2021)
The emergence of various modern and avant-garde musical trends in Argentina throughout the first half of the 20th century triggered numerous publications in music journals of the time that addressed this topic. In this article, we are going to analyze the paper entitled “La música contemporánea y sus problemas” (Contemporary music and its problems) by the Argentine music critic Leopoldo Hurtado, included in no. 11 of Revista de Arte, published in 1936. According to Hurtado, the traditional reception canons of concert music had been modified upon the arrival of new music, thus leading to a detachment between this and the general audience, and reflecting upon social and aesthetic characteristics of the new music trends of the time.Our work centers particularly on this particular paper by Leopoldo Hurtado, complemented by other of his articles, in which he reinforces his ideology in the field of aesthetics over the course of the 1930s and in the early 1940s. Likewise, we establish a dialogue with the ideas expressed by Juan Carlos Paz in another paper published in the same number of the journal to contrast both perspectives.
Keywords: avant-garde music; Argentina; first half of the 20th century; Leopoldo Hurtado; aesthetic